EFFECTS OF MATRINE ON JAK-STAT SIGNALING TRANSDUCTION PATHWAYS IN BLEOMYCIN-INDUCED PULMONARY FIBROSIS - Ma, Xiuqin; Chen, Ruhua; Liu, Xiufang; Xie, Jin; Si, Keyun; Duan, Lirong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The current study aims to investigate the effects of matrine on the JAK-STAT signaling transduction pathways in bleomycin (BLM)-induced pulmonary fibrosis (PF) and to explore its action mechanism. A total of 72 male C57BL/6 mice were randomized into the control, model, and treatment groups. PF models were established by instilling BLM intratracheally. The treatment group was given daily matrine through gastric lavage. Six mice were sacrificed in each group at 3, 7, 14, and 28 days. The lung tissues were observed using hematoxylin-eosin staining. The expression of JAK, STAT1, and STAT3 was observed using immunohistochemistry and then determined using real-time polymerase chain reaction. Alveolitis and PF significantly improved in the treatment group compared with the model group (P < 0.05). The expression of JAK, STAT1, and STAT3 in the model group increased at day 7, peaked at day 14 and then decreased, but the expression was still higher than that in the control group at day 28 (P < 0.05). The three indices in the treatment group were significantly lower than those in the model group at any detection time point (P < 0.05). PF causes high expression of JAK, STAT1, and STAT3. Matrine exerts an anti-PF effect by inhibiting the JAK-STAT signaling transduction pathways.